The Collision Avoidance and Situation-Aware Media Access Scheme Using the Registered-Backoff-Time Method for the IEEE 802.11ah-Based IoT Wireless Networks. (3rd May 2021) - Cheng, Rung-Shiang; Li, Yin-Ming; Huang, Chung-Ming
Abstract: IEEE 802.11ah is a new protocol designed for Internet of Things (IoT). IEEE 802.11ah uses a hierarchical ID assignment schema and designs the corresponding channel access method such that stations can access channel alternatively through the four-level's hierarchical channel access structure. Nevertheless, collisions still cannot be effectively avoided in a dense IOT networking environment using the legacy IEEE 802.11ah. The work proposed the registration-based situation-aware access extension (RSAE) control scheme to avoid collisions, decrease backoff's waiting time and improve slot utilization through the following two ways: (i) in contrast to the traditional CSMA/CA protocol that generates the backoff time for the next channel access after the collision happened, registering the backoff time to AP for scheduling the next channel access before the collision happens; (ii) extending the channel accessing's privilege of those stations that did not complete the data transmission/receiving in the current slot to the available time of the next slot. Comparing with the legacy IEEE 802.11ah, the performance evaluation of the proposed RSAE scheme shown that it still can have a better throughput and a lower collision rate when there is a bigger number of stations in a slot.